Work-family conflict and ethical orientation as predictors of auditor turnover intention: The mediating role of job satisfaction - Putri, Sri Yuli Ayu (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
The present research investigates the influence of Work-Family conflict and ethical orientation on auditors’ turnover intentions, while also examining the mediating role of job satisfaction. Employing a quantitative methodology, the study surveyed 90 married auditors affiliated with public accounting firms (KAPs) in Jakarta. The data were analyzed using Partial Least Squares Structural Equation Modeling (SEM–PLS) to assess the proposed direct and indirect relationship. The empirical result indicated that higher levels of Work-Family conflict significantly increase auditors’ turnover intentions. Ethical orientation, on the other hand, was found to positively enhance job satisfaction, although its direct effect on turnover intentions was not significant. Furthermore, job satisfaction did not significantly mediate the relationships between Work-Family conflict, ethical orientation, and turnover intentions.